ISOLASI DAN IDENTIFIKASI JAMUR PATOGEN BUAH STROBERI SELAMA PENYIMPANAN: - Paisal Ansiska; Selviana Anggraini; Indriati Meilina Sari; Ela Hasri Windari; Hefri Oktoyoki (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2023)
[ISOLATION AND IDENTIFICATION OF STRAWBERRY FRUIT PATHOGENIC FUNGI DURING STORAGE]. Storing strawberry fruit is one way to extend its shelf life and maintain its quality during storage. However, during storage, there is still a risk of pathogenic fungi attack that can cause damage to the strawberry fruit. Pathogenic fungi attack on fruits can cause various types of damage, such as physical damage, color changes, loss of taste and aroma, as well as a decrease in nutritional quality. In addition, pathogenic fungi can also cause significant economic losses for farmers and producers. The purpose of this study is to identify the types of pathogenic fungi commonly found on strawberry fruit and analyze the severity of damage caused by pathogenic fungi. Identification of fungal species is carried out using microscopic methods and through examination of spore morphology. The pathogenic fungi that attack strawberry fruit are Penicillium spp., Colletotrichum spp., and Botrytis cinerea. Strawberry fruit stored at a cool temperature can suppress post-harvest disease symptoms compared to those stored at room temperature.